Food utilization and fecundity of Guppy (Lebistes reticulates) fed with bioencapsulated Artemia franciscana - V. Kanagasabapathi2*and V. Prabhakaran3, M. Vigneeswaran1, (Journal of Ecobiotechnology, 2010)
<span style="font-size: 10pt; line-height: 110%; font-family: ";Garamond";,";serif";; mso-fareast-font-family: SimSun; mso-fareast-language: ZH-CN; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;">The feeding physiology of Lebistes reticulates fed on bioencapsulated Artemia franciscana were investigated under laboratory conditions. Multifactorial experimental designs were used to study food utilization and fecundity. Pre-adult individuals of A. franciscana were enriched with herbal products having aphrodisiac and tonic characters. In the present work herbal products of Withania sominifera and Tinospora cordifolia, were mixed to prepare Compound-I and Myristica fragrans and Terminalia belerica, were mixed to prepare Compound-II, 100% enrichment of Artemia with both compounds were fed to the L. reticulates, the gross and net conversion efficiency in fish L. reticulates fed with bioencapsulated Artemia was found to the more than control. The medicinal plant products having aphrodisiac and tonic characteristics play a significant role in enhancing growth and increasing fecundity of L. reticulates. <span style="font-size: 10pt; line-height: 110%; font-family: ";Garamond";,";serif";; mso-fareast-font-family: SimSun; mso-fareast-language: ZH-CN; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;"> Food utilization and fecundity of Guppy (Lebistes reticulates) fed with bioencapsulated Artemia franciscana M. Vigneeswaran1, V. Kanagasabapathi2*and V. Prabhakaran3 1Department of Zoology V.H.N.S.N. College, Virudhunagar, India 2Department of Zoology, Unit of Aquaculture and Cryobiology, University of Madras, Chennai 600 025, India 3Venture Institute of Biotechnology and Bioinformatics Research, Madurai-4, India *Corresponding Author, Email:Ã‚Â sabapathiÃ‚Â_mu@yahoo.co.in; Phone- +91-9940371267; Fax- +91-416-224-3092 Cite this Article as: M. Vigneeswaran, V. Kanagasabapathi and V. Prabhakaran. 2010. Antifungal and haemolytic activities of organic extracts of Tecoma stans (Bignoniaceae). J. Ecobiotechnol. 2(2): 33-40. Ã‚Â